Design of Ni/NiO–TiO2/rGO nanocomposites on carbon cloth conductors via PECVD for electrocatalytic water splitting. (13th November 2020) - El-Maghrabi, Heba H.; Nada, Amr A.; Roualdes, Stéphanie; Bekheet, Maged F.
Abstract: The facile synthesis and design of noble metal-free efficient catalysts to accelerate the sluggish kinetics of the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) is still a big challenge for electrolytic water splitting. In that context, the preparation of efficient catalysts with superior catalytic activity from cheap raw materials on a large scale is crucial. Briefly, Ni/NiO/TiO2 /rGO is designed using the environmental-friendly and easily up-scalable PECVD technique. This trinary composite presents significance in regulating the crystalline structure, composition and electronic properties towards superior HER and OER activity in acidic solution as bifunctional electrocatalysts for efficient water splitting. Together with the promising long-term stability and durability, Ni/NiO/TiO2 /rGO displays excellent electrocatalytic activity towards HER with η10 of 130 mv vs RHE and a Tafel slope of 40 mV/dec. Graphical abstract: Image 1 Highlights: Facile synthesis of novel Ni/NiO–TiO2 /rGO nanocomposites on carbon cloth via PECVD. Flexible electrodes @ carbon cloth are bifunctional for both OER and HER reactions. The designed electrodes show long-term stability and durability. The electrodes exhibits high electrocatalytic activity for HER with η10 of 130 mV.